Sodium-glucose Cotransporter 2 Inhibitors in Kidney Transplant Recipients – A Retrospective Single Center Study - Freitas, Joana; Francisco, José Teixera; Coimbra, Miguel Trigo; Carvalho, Renata; Vilela, Sara; Silvano, José Luís; Ribeiro, Catarina; Malheiro, Jorge; Pedroso, Sofia; Almeida, Manuela; Fonseca, Isabel; Martins, La Salete (Brazilian Journal of Transplantation, 2024)
Introduction: Considering the rising occurrence of posttranplant diabetes and the elevated cardiovascular burden among transplant recipients, the utilization of SGLT2 inhibitors (SGLT2i) in this group is appealing because of their cardiovascular and renoprotective benefits. Nevertheless, there is a scarcity of evidence for diabetic kidney transplant recipients (DKTRs) owing to concerns about potential renal graft damage and adverse effects. Methods: This retrospective study was devised to assess the effectiveness and safety of SGLT2i in kidney transplant recipients (KTRs). The main focus was on evaluating their impact on parameters such as haemoglobin A1c levels, body mass index (BMI), lipid panel, haemoglobin levels, renal allograft function (estimated glomerular filtration rate) and urirnary protein-to-creatinine ratio. Results: A total of 75 renal transplant patients were included in this investigation. The study spanned a median observation period of 18 (2.0–71.0) months. Median estimated glomerular filtration rate at baseline was 61,9 (26–120) mL/min/1.73 m2 and remained stable throughout the follow-up. Median HbA1c decreased from 7.5 to 7.0% (95% CI; p<0,002). A significant improvement in BMI (95% CI; p<0,001) and lipid panel (95% CI; p<0,05) were also observed. Median haemoglobin rate at baseline was 13,5g/dL and modestly improved at end of follow-up to 13,7g/dL (p=0,12). Regarding urinary protein:creatinine ratio, levels slightly but not significantly rose [+0.05 g/g (p=0,9)]. In a post-hoc subgroup analysis, the rate of urinary tract infections was low (10%). No other side effects were observed during the treatment course. Conclusions: This study demonstrates that the administration of SGLT2i is viable and well-tolerated, with no notable side effects observed in KTRs. However, the question of whether SGLT2i can effectively lower cardiovascular mortality and enhance allograft survival in these patients remains to be explored in subsequent studies.